THE INFLUENCE OF CAR, NIM, ROE, LDR AND NPL ON PROFIT GROWTH AT PT. BANK NEGARA INDONESIA Tbk PERIOD 2018-2022 - Enjel Luciantika Arnedy; Syntha Noviyana (Bisnis Manajemen dan Keuangan, 2024)
The aim of this research is to determine and analyze the influence of financial ratios on profit growth at PT. Bank Negara Indonesia Tbk. The variables used are financial ratios in the period 2018 to 2022 using secondary data from PT's quarterly report. Bank Negara Indonesia Tbk. SPSS version 25 was used to process the data, with multiple linear regression testing. The independent variables in this research are Capital Adequacy Ratio (CAR), Net Interest Margin (NIM) Return on Equity (ROE), Loan to Deposit Ratio (LDR) and Non-Performing Loans (NPL). The methods used in this scientific writing are Descriptive Analysis, Normality Test, Multicollinearity Test, Heteroscedasticity Test, Autocorrelation Test, Multiple Linear Regression Analysis, F Statistical Test, T Statistical Test and Determination Coefficient Analysis (R2). The research results show that the variables NIM, ROE and NPL partially have no effect on PT's profit growth. Bank Negara Indonesa Tbk, while the CAR and LDR variables partially influence PT's profit growth. Bank Negara Indonesia Tbk. In simultaneous testing, the variables CAR, NIM, ROE, LDR and NPL influence PT's profit growth. Bank Negara Indonesia Tbk. The research results also show that the Adjusted R Square value is 0.614 or 61.4%. This means that the five independent variables, namely CAR, NIM, ROE, LDR and NPL, can explain the relationship to the dependent variable, namely profit growth of 61.4, while the remaining 0.386 or 38.6% is explained by other variables which are not included in the regression model of this research.